2020
DOI: 10.3138/jvme.0718-085
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Feline Medial Saphenous Venipuncture Model and Rubric

Abstract: Cats are extremely popular pets with the reputation of being uncooperative for even common procedures, such as venipuncture. In this study, we sought to create and validate a cat medial saphenous venipuncture model and rubric for use in veterinary training. The validation framework consisted of content evidence, internal structure evidence, and relationship with other variables. Eleven veterinarians and veterinary technicians who were experienced with the procedure evaluated the model by means of a survey. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…For TEG and ROTEM, veterinary guidelines suggest the use of a jugular vein and a 21 G or larger needle. 2 Similar recommendations have yet to be developed for the VCM Vet, and saphenous venipuncture may be preferable for fractious cats, 7 or patients with suspected coagulopathies. 8 In dogs, jugular and saphenous citrated samples did not produce significantly different results when analyzed by kaolin-activated TEG, 9 but site of venipuncture has not been compared in cats.…”
Section: Introductionmentioning
confidence: 99%
“…For TEG and ROTEM, veterinary guidelines suggest the use of a jugular vein and a 21 G or larger needle. 2 Similar recommendations have yet to be developed for the VCM Vet, and saphenous venipuncture may be preferable for fractious cats, 7 or patients with suspected coagulopathies. 8 In dogs, jugular and saphenous citrated samples did not produce significantly different results when analyzed by kaolin-activated TEG, 9 but site of venipuncture has not been compared in cats.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the simulator developed in our research, the reproduction of the simplified anatomy was sufficient for the peripheral venipuncture procedure to be performed as many times as necessary, which corroborates with the findings of other authors. It is important to note, however, that further training on the patient is essential [28].…”
Section: Discussionmentioning
confidence: 99%
“…Small animal surgical simulators, such as those described for feline and canine ovariohysterectomy, allow students multiple opportunities to practice routine veterinary surgeries in a lowstakes environment without the use of animals (8)(9)(10). Recent reports on newly developed canine and bovine castration models show positive survey feedback from both veterinary students and clinicians, with both groups reporting that models were useful for surgical skills training (11,12). Hunt et al reported that student performance scores on a canine pre-scrotal closed castration model were strongly correlated with their live castration performance (11).…”
Section: Introductionmentioning
confidence: 99%
“…Given the wealth of evidence for the potential educational, ethical, practical, and financial advantages of models/simulators for veterinary student surgical training (9,11,12,(14)(15)(16), and the lack of an available equine castration model, we sought to develop a low-fidelity model of closed equine castration as performed on a "cast" or recumbent horse. The specific goals for this project were to create an affordable simulator and associated formative assessment that allowed students a chance to: (1) practice a cognitive, step-wise approach to equine field castration, (2) recognize their own strengths and weaknesses when performing a clinical procedure, and (3) receive timely and specific expert feedback on this skill.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation